Modification of lysine deacetylation regulates curcumol‐induced necroptosis through autophagy in hepatic stellate cells. (11th May 2022) - Sun, Sumin; Li, Zhanghao; Huan, Sheng; Kai, Jun; Xia, Siwei; Su, Ying; Ji, Shufan; Chen, Anping; Wang, Shijun; Xu, Xuefen; Shao, Jiangjuan; Zhang, Feng; et al.
Abstract: The excessive deposition of extracellular matrix (ECM) is the main characteristic of liver fibrosis, and hepatic stellate cells (HSCs) are the main source of ECM. The removal of activated HSCs has a reversal effect on liver fibrosis. Western blot and MTT analysis indicated that curcumol could relieve hepatic fibrosis by promoting HSCs receptor‐interacting protein kinase 1/3 (RIP1/RIP3)‐dependent necroptosis. Importantly, autophagy flow was monitored by constructing the mRFP‐GFP‐LC3 plasmid, and it was found that curcumol cleared activated HSCs in a necroptosis manner that was dependent on autophagy. Our study suggested that the activation of necrosome formed by RIP1 and RIP3 depended on Atg5, and that autophagosomes were also necessary for curcumol‐induced necroptosis. Furthermore, microscale thermophoresis and co‐immunoprecipitation assay results proved that curcumol could target Sirt1 to regulate autophagy by reducing the acetylation level of Atg5. The HSCs‐specific silencing of Sirt1 exacerbated CCl4 ‐induced liver fibrosis in mice. The deacetylation of Atg5 not only accelerated the accumulation of autophagosomes but also enhanced the interaction between Atg5 and RIP1/RIP3 to induce necroptosis. Overall, our study indicated that curcumol could activate Sirt1 to promote Atg5 deacetylation and enhanced its protein–protein interaction function, thereby inducing autophagy and promoting the necroptosis of HSCs to reduce liver fibrosis.